2015
DOI: 10.1021/acsnano.5b02902
|View full text |Cite
|
Sign up to set email alerts
|

Use of Synergistic Interactions to Fabricate Strong, Tough, and Conductive Artificial Nacre Based on Graphene Oxide and Chitosan

Abstract: Graphene is the strongest and stiffest material, leading to the development of promising applications in many fields. However, the assembly of graphene nanosheets into macrosized nanocomposites for practical applications remains a challenge. Nacre in its natural form sets the "gold standard" for toughness and strength, which serves as a guide to the assembly of graphene nanosheets into high-performance nanocomposites. Here we show the strong, tough, conductive artificial nacre based on graphene oxide through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
192
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 251 publications
(203 citation statements)
references
References 34 publications
10
192
0
1
Order By: Relevance
“…The interface in the nacre induces multiple toughening mechanism, such as mineral bridging, nanoasperities shearing, organic gluing, and tablet interlocking, [1] as shown in Figure 3. [122][123][124][125][126][127][128] In addition, different interface interactions could be reasonably combined to result in synergistic effect, [111,[129][130][131][132][133][134][135][136][137][138][139] which is similar to the multiple interface interactions in nacre. [48,75,[91][92][93][94] The interfacial crosslinking strategies contain hydrogen bonding, [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] ionic bonding, …”
Section: Interfacial Architecture Of Biological Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…The interface in the nacre induces multiple toughening mechanism, such as mineral bridging, nanoasperities shearing, organic gluing, and tablet interlocking, [1] as shown in Figure 3. [122][123][124][125][126][127][128] In addition, different interface interactions could be reasonably combined to result in synergistic effect, [111,[129][130][131][132][133][134][135][136][137][138][139] which is similar to the multiple interface interactions in nacre. [48,75,[91][92][93][94] The interfacial crosslinking strategies contain hydrogen bonding, [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] ionic bonding, …”
Section: Interfacial Architecture Of Biological Materialsmentioning
confidence: 98%
“…When the hydrogel is on loading, the Ca 2+ bridged GO network effectively dissipates the crack energy through unzipping and/or sliding of the weak ionic bonding or the deformation of the network conformation, while the hydrogen bonding between GO network and covalent PAM network contributes to maintaining the structural integrity of the hydrogel. [130] Copyright 2015, American Chemical Society. Compared with GO-PAM hydrogels (66%) without Ca 2+ , the compression strain of GO-Ca 2+ -PAM hydrogels with optimal weight ratio of Ca 2+ /GO of 204% is increase to 94% under the same compression stress of 0.4 MPa.…”
Section: Hydrogen Bonding and Ionic Bondingmentioning
confidence: 99%
“…[15] Copyright 2016, Wiley-VCH; Flexible-membrane SEM image: reproduced with permission. [16] Copyright 2015, American Chemical Society; Ceramic-based nanocomposite SEM image: reproduced with permission. [17] Copyright 2016, The American Association for the Advancement of Science; and Anisotropic hydrogel image: reproduced with permission.…”
Section: Interface Interactionsmentioning
confidence: 99%
“…These bioinspired reduced GO-PDA nanocomposites show simultaneous enhancement in tensile strength and toughness. Recently, Wan et al [16] demonstrated high-performance bioinspired rGO-CS nanocomposite film via synergistic interface interactions of hydrogen and covalent bonding. The lateral fracture morphology of rGO-CS showed a clear pull-out and curved edges of rGO nanosheets, as shown in Figure 7A 1 .…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation